FORMULASI DAN UJI STABILITAS FISIK SEDIAAN LULUR BODY SCRUB EKSTRAK ETANOL KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Dewi Fitriani Puspitasari (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2023)
Stability is an important thing to maintain in a preparation. Red dragon fruit skin (Hylocereus polyrhizus) is a part of the dragon fruit that contains a natural dye called anthocyanin. This substance can be used as an anti-aging agent because of its antioxidant properties. Anthocyanins are known to be unstable compounds due to the influence of temperature.This study aims to formulate body scrub preparations by utilizing anthocyanin compounds contained in red dragon fruit peels, as well as knowing the physical characteristics and physical stability of preparations stored at 4°C, 25°C and 40°C. The body scrub is made using the ethanol extract of dragon fruit cultivar at a concentration of 15%. Testing the physical characteristics of the preparation includes organoleptic, homogeneity, spreadability, adhesion, viscosity, pH and cream type. The physical stability test of the preparation was stored at ± 4°C, 25°C and 40°C for 30 days. The results showed that red dragon fruit peel extract (Hylocereus polyrhizus) which was formulated in the form of a body scrub had a fairly good stability during the storage process. Conclusion: Red dragon fruit peel extract (Hylocereus polyrhizus) has good stability in body scrub preparations